2018
DOI: 10.1504/ijtm.2018.093943
|View full text |Cite
|
Sign up to set email alerts
|

Equity crowdfunding in technology transfer strategies and licensing

Abstract: The main aim of this study is to investigate to what extent equity crowdfunding could enable firms to outsource research and development activities. Likewise, the present study aims at analyzing the relationship between desorptive capacity and equity crowdfunding performance. We also aim at studying the mediation role of ICT firms capabilities, connective capacity and minor equity ownership. In this regard, this study intends to pioneer into connecting the knowledge management theory with the crowdfunding stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
2
9
0
1
Order By: Relevance
“…For example, buying firms could visit the suppliers' premises and support them in training and quality management or even locate their own employees to help suppliers rebound from the disruption caused by a risk. Moreover, due to the limited access to key resources, many SMEs do not possess in‐house R&D. However, reciprocal sharing of scientific and technological knowledge and joint investments within supply chain partners can enable them to innovate together and achieve better performance (Dezi, Cillo, Usai, & Pisano, 2018; Knudsen, 2007). Thus, improved knowledge sharing among business partners can reduce the impact of operational risks on supply chain (i.e., FSCs) performance through smoother product flow, better decision making, reduction in supply–demand issues and chances of operational glitches.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…For example, buying firms could visit the suppliers' premises and support them in training and quality management or even locate their own employees to help suppliers rebound from the disruption caused by a risk. Moreover, due to the limited access to key resources, many SMEs do not possess in‐house R&D. However, reciprocal sharing of scientific and technological knowledge and joint investments within supply chain partners can enable them to innovate together and achieve better performance (Dezi, Cillo, Usai, & Pisano, 2018; Knudsen, 2007). Thus, improved knowledge sharing among business partners can reduce the impact of operational risks on supply chain (i.e., FSCs) performance through smoother product flow, better decision making, reduction in supply–demand issues and chances of operational glitches.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The scope and structure of this collaboration is a very important strategic decision based on the fact that the value chain in the agri-food sector is characterized by a flow of information exchanged within the company along with suppliers and customers (Christopher, 1998). Moreover, due to the lower innovation-absorption capabilities and to the limited resources for in-house RandD, companies need to develop a broad network of partners which can give them scientific and technological inputs (Knudsen, 2007;Dezi et al, 2018). This is the reason why nowadays information and communication technologies allow a fast and worldwide data and information, and associate a pivotal role to knowledge sharing (KS) practices within a company (Lin, 2007;Sá enz et al, 2009;Pee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies on the role of social capital in equity-based crowdfunding (Dezi et al , 2018; Vismara, 2016). Conducting a survey in the UK market, Baeck et al (2014) found that social network connections are important for the success of 67% of fundraising campaigns.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hornuf and Schwienbacher, 2018a) on EC platforms, frequently analyzing a single platform (e.g. Lukkarinen et al , 2016; Mohammadi and Shafi, 2018; Vismara, 2018) and rarely multi-platforms (Hornuf and Schwienbacher, 2018b; Dezi et al , 2018). However, with regards to the general topic of intellectual capital, the literature on EC is still scarce, and some researchers analysed the topic with reference specifically to human capital (Piva and Rossi-Lamastra, 2018; Barbi and Mattioli, 2019).…”
Section: Introductionmentioning
confidence: 99%